2019
DOI: 10.1037/cdp0000231
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Mexican-origin adolescents’ bicultural competence and mental health in context.

Abstract: Objectives:We examined the prospective association (from M age ϭ 15.84 to 17.38 years) between bicultural competence and mental health among U.S. Mexican-origin adolescents relative to multiple (a) developmental niches, (b) components of bicultural competence, and (c) indicators of mental health. Method: Participants included 749 adolescents (49% female, 29.7% Mexico-born) recruited during late childhood and followed through late adolescence. We used latent profile analyses to identify adolescents' development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 75 publications
1
43
0
Order By: Relevance
“…Bicultural individuals have internalized two cultural knowledge systems (e.g., heritage and host; Benet-Martínez, Leu, Lee, & Morris, 2002) and developed bicultural competence , the ability to function successfully within bicultural contexts (LaFromboise, Coleman, & Gerton, 1993). Though bicultural competence is a normative developmental competency among ethnic-racial minority and immigrant adolescents (Safa et al, 2019), little is known about family processes that promote or inhibit its development. This gap is especially problematic in the developmental period spanning late childhood to late adolescence, across which youths are gaining increasing cognitive abilities (Arnett, 2014) that support comprehension of complex, culturally situated demands associated with different cultural systems (Knight, Safa, & White, 2018).…”
mentioning
confidence: 99%
“…Bicultural individuals have internalized two cultural knowledge systems (e.g., heritage and host; Benet-Martínez, Leu, Lee, & Morris, 2002) and developed bicultural competence , the ability to function successfully within bicultural contexts (LaFromboise, Coleman, & Gerton, 1993). Though bicultural competence is a normative developmental competency among ethnic-racial minority and immigrant adolescents (Safa et al, 2019), little is known about family processes that promote or inhibit its development. This gap is especially problematic in the developmental period spanning late childhood to late adolescence, across which youths are gaining increasing cognitive abilities (Arnett, 2014) that support comprehension of complex, culturally situated demands associated with different cultural systems (Knight, Safa, & White, 2018).…”
mentioning
confidence: 99%
“…First, mothers’ perceptions may not match adolescents’ perceptions of neighborhood social and cultural cohesion. Thus, adolescents may view their neighborhoods differently and, possibly, view the shared values and Mexican customs as inhibiting their opportunities to explore what it means to be both Mexican and American, which can both be parts of their ethnic self-concepts (Flores-González et al, 2014; Knight et al, 2018; Safa et al, 2019). Second, and related to the first, the meaning of the fifth-grade neighborhood context for adolescents’ 10th-grade ERI exploration may be reduced or altered by developmental changes that take place between late childhood and middle adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected, therefore, that ERI resolution, attained via ERI exploration, will promote the development of all three components of global bicultural competence. However, individuals do not often achieve the same degree of competence across all bicultural skills and components (David et al, 2009;Safa et al, 2019) and prior work has suggested that bicultural facility and comfort differentially predict adjustment (Safa et al, 2019). Thus, it is important to consider that the associations between ERI developmental processes and each global bicultural competence component may not be the same.…”
Section: Eri Development and Global Bicultural Competencementioning
confidence: 99%
“…These findings suggest that the same processes may be promoting the development of different facets (e.g., behavioral, affective) of bicultural competence. Furthermore, greater behavioral, affective, and cognitive components of bicultural competence have been associated with higher adjustment (e.g., general self-efficacy, prosocial tendencies, life satisfaction, and selfesteem; Carlo et al, 2016;David, Okazaki, & Saw, 2009) and with lower maladjustment (e.g., internalizing and externalizing symptoms; Carrera & Wei, 2014;Safa et al, 2019;Wei et al, 2010). Thus, we focus on bicultural facility, comfort, and advantage, given their theorized relevance for the development of behavioral, affective, and cognitive bicultural skills and because of their promoting influence on adjustment.…”
Section: Eri Development and Global Bicultural Competencementioning
confidence: 99%